The limitations of market-based approaches to empowerment: lessons from a case study in Northern Ghana. Issue 6 (18th August 2019) - Friedson-Ridenour, Sophia; Clark-Barol, Molly; Wilson, Kurt; Shrestha, Sweta; Ofori, Cassandra Mercy
ABSTRACT: The international development community is focusing on women's empowerment as a key means of achieving high-level development goals. In this context, many development programmes, such as Feed the Future, take a market-based approach to empowerment focusing on access to and control over resources as the primary drivers of change. This kind of empowerment programming, however, often loses sight of power relations which structure access to resources and opportunities. This article, therefore, explores the limitations of economic-based approaches to empowerment that permeate the international development space, and provides strong evidence that a broader multi-dimensional approach is needed to support women's empowerment.